Energy Crisis in Pakistan : Origins, Challenges and Sustainable Solutions - Asif, Muhammad; Foreword by Yunus, Muhammad (Karachi Oxford University Press, 2012)
The book primarily aims to educate various stakeholders of society (i.e. policy and decision makers, energy circles, academia, business community, NGOs and civil society) on the subject of energy, particularly in the wider context of the energy crisis facing Pakistan. In a global perspective, it presents an account of the key dimensions of energy in the modern age. Having discussed the energy challenges facing Pakistan, the book provides recommendations and policy guidelines to achieve energy prosperity in the country. It has a holistic, yet easy to follow approach. It presents a coherent blend of the technical and the social aspects of energy. Using appealing diagrams and data presentations, it explains the subject in a reader-friendly way. Referring to examples and citing case studies from developed as well as developing countries it offers plenty of food for thought to its audience. The foreword to the book has been written by Dr Muhammad Yunus, the winner of the 2006 Nobel Peace Prize.
Include Illustrations, Figures, Glossary and Index.
The book presents a detailed analysis of the nature and the implications of the ongoing energy crisis in Pakistan. In this regard the role of pertinent stakeholders has been critically reflected upon. Highlighting the key strengths of the national energy base, solutions have been suggested to achieve a sustainable energy future for the country.
Keywords: Power Resources -- Energy Policy -- Renewable Energy Sources